Four new species of dragon pseudoscorpions (Pseudoscorpiones: Pseudotyrannochthoniidae: Spelaeochthonius) from caves in South Korea revealed by integrative taxonomy - Kyung–Hoon Jeong; Danilo Harms; Jung-sun Yoo; Sora Kim (PLoS ONE, 2025)
Karst research in Korea is still in its infancy and the invertebrate fauna of subterranean systems across the country is poorly known. One of the very diverse lineages in caves across Korea, the pseudoscorpions, are almost undocumented although they represent stunning examples of cave adaptations and troglomorphism. In this study, we provide a phylogenetic hypothesis for the pseudoscorpion Spelaeochthonius Morikawa, 1954 (Pseudoscorpiones: Pseudotyrannochthoniidae) in South Korea; a genus that exclusively occurs in caves across China, Japan and the Korean Peninsula. We report seven species of which four are newly described and illustrated based on molecular, distributional and morphological data: Spelaeochthonius dugigulensis sp. nov., S. geumgulensis sp. nov., S. magwihalmigulensis sp. nov. and S. yamigulensis sp. nov. All species are strongly cave-adapted and known from a single cave or karst system only, emphasizing the need to implement conservation strategies for Korean karst systems and their fauna.